2010
DOI: 10.1002/ange.200907274
|View full text |Cite
|
Sign up to set email alerts
|

Amide‐to‐Ester Substitution Allows Fine‐Tuning of the Cyclopeptide Conformational Ensemble

Abstract: Supporting information for this article (experimental details of cyclodepsipeptide syntheses, cellular assays, structure analysis and calculations, characterization of compounds, and MD calculations) is available on the WWW under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…The FESs of c(‐RGDf(NMe)V‐) and CDGRC indicate that more than 90 % of the structures are contained in the β L and α L regions, respectively, whereas CisoDGRC populates the three isoenergetic regions β L , β P , and α (Table 1). Interestingly, in the β L minimum, the Gly ϕ and ψ angles of c(‐RGDf(NMe)V‐) structures are similar to those observed for the cyclopeptide bound to the αvβ3 receptor (Table 1), which is consistent with the fact that the amide groups of Gly and the following residue point in opposite directions 2628. In contrast, in CDGRC this alternate conformation is not fulfilled, which contributes to its inability to bind αvβ3 25.…”
Section: Population Distribution and Energetic And Geometric Charactesupporting
confidence: 77%
“…The FESs of c(‐RGDf(NMe)V‐) and CDGRC indicate that more than 90 % of the structures are contained in the β L and α L regions, respectively, whereas CisoDGRC populates the three isoenergetic regions β L , β P , and α (Table 1). Interestingly, in the β L minimum, the Gly ϕ and ψ angles of c(‐RGDf(NMe)V‐) structures are similar to those observed for the cyclopeptide bound to the αvβ3 receptor (Table 1), which is consistent with the fact that the amide groups of Gly and the following residue point in opposite directions 2628. In contrast, in CDGRC this alternate conformation is not fulfilled, which contributes to its inability to bind αvβ3 25.…”
Section: Population Distribution and Energetic And Geometric Charactesupporting
confidence: 77%
“…) with ester link between N ‐Val and Arg showed increased potency with respect to the parent compound, being a potent small‐molecule dual αvβ3 and αvβ5 antagonist in cell adhesion assays, IC 50 αvβ3/FN = 1.0 × 10 −7 M, IC 50 αvβ5/VN = 6.0 × 10 −8 M, respectively, compared to IC 50 = 3.2 × 10 −7 and 2.0 × 10 −7 M for cilengitide under the same conditions. As another example, the N ‐Me group was replaced by N ‐oligoethylene glycol (N‐OEG) of increasing length to provide the more lipophilic bioactive analogs 6 (Fig. ) …”
Section: Integrins and Their Ligandsmentioning
confidence: 99%
“…[15][16][17] A previous report about conformational studies of a cyclic RGD peptide showed that peptides with amide-to-ester substitutions can form similar conformations with original peptides. 18 Another report showed that a reverse ester-toamide substitution on the backbone of a bioactive peptide did not affect its inhibitory activity in vitro, but significantly reduced its inhibitory activity in cells, 19 indirectly suggesting that the ester-to-amide substitution reduces the membrane permeability of this peptide. Considering these reports, amide-to-4 ester substitution of a proper amide bond is expected to improve the passive membrane permeability of a peptide and, at the same time, allow the modified peptide to form similar conformations with the original peptide.…”
Section: Introductionmentioning
confidence: 99%